The Influence of Knowledge of Zakat, Income Level and Trust in Muzakki's Interest in Paying Zakat on Agricultural Products through Baznas Kampar Regency - Sastraningsih, Ellyan; Wahyuningsih, Eny; Ahmad, Rahayati (Universitas Islam Negeri Raden Intan Lampung, 2023)
The reason for this thought is to find out the effect of zakat information, payment rate, and confidence on the interest of muzakki to pay zakat assets to Baznas Kampar Regency. This research was conducted in Kampar Regency. To analyze collected data, the SPSS application was utilized. A total of 98 primary data collected using a questionnaire with the Slovin sampling method. Respondents in this study were Muzakki who were affiliated with BAZNAS Kampar Regency. According to the study, knowledge about zakat has a significant impact on their willingness to pay zakat, income level has a significant impact on their willingness to pay zakat, and trust has a positive impact on their willingness to pay agricultural zakat.